Multi-isotopic analysis reveals the early stem turtle Odontochelys as a nearshore herbivorous forager - Goedert, Jean; Amiot, Romain; Anquetin, Jérémy; Séon, Nicolas; Bourgeais, Renaud; Bailly, Gilles; Fourel, François; Simon, Laurent; Li, Chun; Wang, Wei; Lécuyer, Christophe (Frontiers in Ecology and Evolution, 2023)
After decades of debate on the origin of turtles, it is now widely accepted that they are diapsid reptiles originating in the Permian from a terrestrial ancestor. It seems that the initial development of the structures that will later form the unique turtle bony shell took place as a response to a fossorial lifestyle. However, the earliest stem turtle with a fully complete plastron, Odontochelys semitestacea from the Late Triassic (lower Carnian) of China, is somewhat controversially interpreted as an aquatic or even a marine form, raising the question of the environment in which the completion of the plastron happened. Here, we analyzed the stable carbon, oxygen and sulfur isotope compositions (δ 13 C, δ 18 O and δ 34 S) of bones from two specimens of Odontochelys along with bones and teeth of two associated specimens of the marine ichthyosaur Guizhouichthyosaurus tangae. We first show that δ 18 O values of Odontochelys are incompatible with a terrestrial lifestyle and imply a semi-aquatic to aquatic lifestyle. Isotopic results also demonstrate that the aquatic environment of Odontochelys was submitted to a strong marine influence, therefore excluding the possibility of a strict freshwater aquatic environment.Additionally, an unusual carbon isotope composition shows that O. semitestacea was herbivorous, probably consuming macrophytic algae in coastal zones like the extant green sea turtle (Chelonia mydas) or the marine iguana (Amblyrhynchus cristatus) do.